Vitamin D Promotes Skeletal Muscle Regeneration and Mitochondrial Health - Latham, Christine M.; Brightwell, Camille R.; Keeble, Alexander R.; Munson, Brooke D.; Thomas, Nicholas T.; Zagzoog, Alyaa M.; Fry, Christopher S.; Fry, Jean L. (Frontiers in Physiology, 2021)
Vitamin D is an essential nutrient for maintenance of skeletal muscle and bone health. The vitamin D receptor (VDR) is present in muscle, as is CYP27B1, the enzyme that hydroxylates 25(OH)D to its active form, 1,25(OH)D. Furthermore, mounting evidence suggests that vitamin D may play an important role during muscle damage and regeneration. Muscle damage is characterized by compromised muscle fiber architecture, disruption of contractile protein integrity and mitochondrial dysfunction. Muscle regeneration is a complex process that involves restoration of mitochondrial function and activation of satellite cells, the resident skeletal muscle stem cells. VDR expression is strongly upregulated following injury, particularly in central nuclei and satellite cells in animal models of muscle injury. Mechanistic studies provide some insight into the possible role of vitamin D activity in injured muscle. In vitro and in vivo rodent studies show that vitamin D mitigates reactive oxygen species (ROS) production, augments antioxidant capacity, and prevents oxidative stress, a common antagonist in muscle damage. Additionally, VDR knockdown results in decreased mitochondrial oxidative capacity and ATP production, suggesting that vitamin D is crucial for mitochondrial oxidative phosphorylation capacity; an important driver of muscle regeneration. Vitamin D regulation of mitochondrial health may also have implications for satellite cell activity and self-renewal capacity, which could further affect muscle regeneration. However, the optimal timing, form and dose of vitamin D, as well as the mechanism by which vitamin D contributes to maintenance and restoration of muscle strength following injury, have not been determined. More research is needed to determine mechanistic action of 1,25(OH)D on mitochondria and satellite cells, as well as how this action manifests following muscle injury in vivo. Moreover, standardization in vitamin D sufficiency cut-points, time-course study of the efficacy of vitamin D administration, and comparison of multiple analogs of vitamin D are necessary to elucidate the potential of vitamin D as a significant contributor to muscle regeneration following injury. Here we will review the contribution of vitamin D to skeletal muscle regeneration following injury.